Youth unrest and riots In France and the UK - (:unkn) unknown (My University, 2012)
In northern Europe, youth demonstrations and riots have recurred during the last three decades. During the late 2000s, social unrest spread mostly in southern European countries but also, more surprisingly, in the UK. Despite important common points, these two countries show striking contrasts in the nature of their protests. In the UK, the rioters were not youth with direct African ancestry, nor Pakistani or Bangladeshi, but rather youth of Black Caribbean ancestry or native Britons from the lower rung of the social ladder, with disproportionately high unemployment rates. In France, the 2005 riots were numerous in the capital region and in cities of the industrial east and southeast. The participants of the riots were mainly youth of African ancestry; for the first time in recent French history, youth whose family came from Sahel Africa were overrepresented. Adolescents belonging to large families, living in areas where close to 50 per cent of the population is under 25 years-old, dominated the 2005 riots. But there was little interethnic strife among minorities.
Keywords: African Research